Pelatihan Guru Penjas tentang Pengembangan Ekstra Bola Voli di Sekolah Menengah Pertama - Sujarwo (JURNAL PENGABDIAN MASYARAKAT OLAHRAGA DAN KESEHATAN (JASO), 2025)
Physical education teachers are hampered by a lack of information about the development of volleyball extracurriculars organized by related parties. The aim of the service is collaboration between the MGMP Penjas Junior High School and the PBVSI Bantul District Management. This service method involves training for physical education teachers for four days using theoretical techniques (lectures, discussions), practice and assignments. The number of participants in this service is: 36 physical education teachers. Evaluation was carried out using pre and post tests on the level of teacher understanding regarding the development of volleyball extracurricular activities in schools. The result of this community service was an increase in the knowledge of PJOK teachers at Junior High Schools in Bantul Regency regarding the development of volleyball extracurricular activities, with a pretest result of: 51.39. After being given training by the service team, there was an increase in the mean of: 76.39. The conclusion is that training or training on developing extracurricular activities in junior high schools for PJOK teachers in Bantul Regency can increase the knowledge of PJOK teachers to develop extra volleyball activities.